All Days 2008
DOI: 10.2118/113314-ms
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behaviour Methods for the Evaluation of Surfactants for Chemical Flooding at Higher Temperature Reservoir Conditions

Abstract: Accurate laboratory screening of surfactants for their ability to give ultra-low interfacial tensions in oil/brine systems is important as a pre-cursor to laboratory core flow tests and surfactant flooding processes in the field. Screening is usually judged by visualisation of middle-phase micro-emulsions in oil/brine systems. Three laboratory methods are described which enable the phase behaviour of oil/water systems containing surfactants to be more safely visualised and measured in glassware at higher tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Barnes et al 16 evaluated the results IOS with different carbon numbers using improved phase behavior experimental methods and showed that IOS family of surfactants had good chemical stability at higher temperatures (up to 150°C) and high solubilization of oil at their optimal salinities. However high critical micelle concentration (CMC) and limited salinity tolerance are the main drawbacks of anionic surfactant, which make them inappropriate for applying at high concentrations of divalent ions 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Barnes et al 16 evaluated the results IOS with different carbon numbers using improved phase behavior experimental methods and showed that IOS family of surfactants had good chemical stability at higher temperatures (up to 150°C) and high solubilization of oil at their optimal salinities. However high critical micelle concentration (CMC) and limited salinity tolerance are the main drawbacks of anionic surfactant, which make them inappropriate for applying at high concentrations of divalent ions 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The substantial shear-thinning flow behavior and suitable values of dynamic viscosities (i.e., viscosity values that are not too high and/or too low relative to the viscosity of the oil) ensure stable microemulsion systems that effectively propagate through the sand-packs, forming a stable displacement front that displaces oil more effectively with a low risk of microemulsion phase fingering and/or trapping within the porous media. 6,12,27,30,53,66 Moreover, in this work, the optimum formulations were prepared by blending a straight chain surfactant (i.e., SDS) and a branched chain surfactant (i.e., Alfoterra 167-4s) that creates disorder in the mixture, avoiding the formation of highly viscous micellar structures (i.e., gel-like phases). 6,21,29,71 Samples of both optimum formulations have been kept for a period of 4 years at room temperature to evaluate the stability of the middle microemulsion phases (i.e., Winsor Type III).…”
Section: Resultsmentioning
confidence: 99%
“…A number of previous papers have characterized this work very well (including: Wade, et al, 1978;Barnes, et al;Solairaj, et al, 2012, etc.). New research on phase behavior and IFT at high temperature ( ~ 120°C) and high salinity ( ~ 20 % TDS) show that: with NaCl and n-octane oil mixed with alkoxyglycidylether (AGES) sulfonate anionic surfactants (free of alcohol and other co-solvents), classical Winsor phase behavior and optimal salinity were observed, providing ultra-low IFTs (Puerto, et al, 2011).…”
Section: Introductionmentioning
confidence: 86%